2011
DOI: 10.1038/jcbfm.2011.160
|View full text |Cite
|
Sign up to set email alerts
|

Poly-IC Preconditioning Protects against Cerebral and Renal Ischemia-Reperfusion Injury

Abstract: Preconditioning induces ischemic tolerance, which confers robust protection against ischemic damage. We show marked protection with polyinosinic polycytidylic acid (poly-IC) preconditioning in three models of murine ischemia-reperfusion injury. Poly-IC preconditioning induced protection against ischemia modeled in vitro in brain cortical cells and in vivo in models of brain ischemia and renal ischemia. Further, unlike other Toll-like receptor (TLR) ligands, which generally induce significant inflammatory respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 15 publications
5
40
0
Order By: Relevance
“…Moreover, the protective effects of poly(I:C) were abolished in the TLR3 2/2 mouse MCAO model, suggesting that the protective effects of poly(I:C) are mediated via TLR3. It has been reported that poly(I:C) preconditioning could reduce I/R injury (17,18), and our results demonstrated that poly(I:C) treatment 3 h after ischemia had therapeutic effects on cerebral I/R injury. However, a recent study has reported that TRL3 activation increased the susceptibility of neonatal brain to hypoxia and ischemia (36).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Moreover, the protective effects of poly(I:C) were abolished in the TLR3 2/2 mouse MCAO model, suggesting that the protective effects of poly(I:C) are mediated via TLR3. It has been reported that poly(I:C) preconditioning could reduce I/R injury (17,18), and our results demonstrated that poly(I:C) treatment 3 h after ischemia had therapeutic effects on cerebral I/R injury. However, a recent study has reported that TRL3 activation increased the susceptibility of neonatal brain to hypoxia and ischemia (36).…”
Section: Discussionsupporting
confidence: 59%
“…Ischemia preconditioning can reduce cerebral I/R injury (35), and recent reports have shown that poly(I:C) preconditioning protects against cerebral I/R injury (17,18). However, it has not been determined whether postischemia poly(I:C) treatment would also be effective in protecting against cerebral I/R injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR agonists may also act directly on BBB at the interface between blood and brain resulting in increased BBB stabilization following ischemia. Adapted from [ 125 ] conventional pharmacotherapy (e.g., thrombolytics and clot removal devices) or enhance the effi cacy of existing partially effective therapeutics. As with many human conditions, brain injury is multifactorial; thus, a single therapeutic, a so-called magic bullet, is not likely to exist for stroke or other brain injuries.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Cole et al [52] demonstrated an unexpected beneficial role for TLR3 in the arterial wall upon systemic administration of poly(I:C). Further, Packard et al [53] found poly(I:C) administration to be protective against cerebral ischemia-reperfusion injury. Since MSCs are widely present in vivo and their perivascular origin in multiple human organs appears certain [5,10] , it is possible that these prophylactic benefits of poly(I:C) may be mediated through its trophic stimulatory effect on the endogenous MSC niches.…”
Section: Competencementioning
confidence: 99%